2008
DOI: 10.1108/13563280810914847
|View full text |Cite
|
Sign up to set email alerts
|

Concise corporate reporting: communication or symbolism?

Abstract: Purpose -Corporate reporting is an important component of the investor relations function, and the aim of this paper is to seek evidence as to whether, as is often assumed, concise financial reports result in clearer communication between the company and its report users. If concise reports are genuinely being prepared in an attempt to improve the clarity of communication with stakeholders, it is to be expected that other disclosures in the annual reports in which they are disseminated should similarly reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 31 publications
1
50
0
2
Order By: Relevance
“…One of the key characteristics of a good report is its ability to convey the necessary information to its wide audience in a way that is easy to read and understand and is appropriate for decision-making (Buitendag, Fortuin, & de Laan, 2017;Chatterjee, 2008;Cook & Sutton, 1995;Eugene Baker III & Kare, 1992;Jones, 1988;Pashalian & Crissy, 1952;Rahman, 2014;Richards & van Staden, 2015). Unfortunately, many studies have found that financial reports are lacking in readability (Anderson, 1998;Bartlett & Chandler, 1997;Hrasky & Smith, 2008;Schroeder & Gibson, 1992), in part as a result of increasing complexity (Eccles & Saltzman, necessarily read corporate reports nor find them useful, which could be a function of reports being difficult to read. Readability is positively associated with effective communication (Courtis & Hassan, 2002;Subramanian, Insley, & Blackwell, 1993) and was found to even affect the outcome of analysts" forecasts (Lehavy, Li, & Merkley, 2011).…”
Section: [Integrated R]eporting Provides Insight Into How a Company Vmentioning
confidence: 99%
“…One of the key characteristics of a good report is its ability to convey the necessary information to its wide audience in a way that is easy to read and understand and is appropriate for decision-making (Buitendag, Fortuin, & de Laan, 2017;Chatterjee, 2008;Cook & Sutton, 1995;Eugene Baker III & Kare, 1992;Jones, 1988;Pashalian & Crissy, 1952;Rahman, 2014;Richards & van Staden, 2015). Unfortunately, many studies have found that financial reports are lacking in readability (Anderson, 1998;Bartlett & Chandler, 1997;Hrasky & Smith, 2008;Schroeder & Gibson, 1992), in part as a result of increasing complexity (Eccles & Saltzman, necessarily read corporate reports nor find them useful, which could be a function of reports being difficult to read. Readability is positively associated with effective communication (Courtis & Hassan, 2002;Subramanian, Insley, & Blackwell, 1993) and was found to even affect the outcome of analysts" forecasts (Lehavy, Li, & Merkley, 2011).…”
Section: [Integrated R]eporting Provides Insight Into How a Company Vmentioning
confidence: 99%
“…and to use more graphs (e.g. Hrasky and Smith, 2008). Bank size was estimated as the natural logarithm of banks' total assets at the end of the financial year.…”
Section: Empirical Modelmentioning
confidence: 99%
“…Hrasky and Smith (2008) assume corporate reporting is an important component of the investor relations function, and they look for evidence as to whether concise financial reports result in clearer communication between the company and its report users. In their study, characteristics of the chairperson's annual report letter and graph use in annual reports containing a concise financial report were compared to those in traditional full reports of listed Australian companies.…”
Section: Annual Reports and Disclosurementioning
confidence: 99%
“…In their study, characteristics of the chairperson's annual report letter and graph use in annual reports containing a concise financial report were compared to those in traditional full reports of listed Australian companies. According to their results, if concise reporters genuinely wish to improve the clarity of their communications, greater attention needs to be paid to how information is presented in their broader annual report (Hrasky & Smith, 2008 (Hutt, 2010). Lin et al (2012) collected the annual reports of the 660 public listed companies in Taiwan and applied content analysis to company annual reports to obtain the disclosure information for human capital.…”
Section: Annual Reports and Disclosurementioning
confidence: 99%
See 1 more Smart Citation